If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 5y = 11 Solving -2x + 5y = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5y' to each side of the equation. -2x + 5y + -5y = 11 + -5y Combine like terms: 5y + -5y = 0 -2x + 0 = 11 + -5y -2x = 11 + -5y Divide each side by '-2'. x = -5.5 + 2.5y Simplifying x = -5.5 + 2.5y
| 18h+63= | | 14f-28= | | -16t^2+96t+112= | | 3x-x+8=-16 | | 14x-13=9x+12 | | 2y^2-y+8=0 | | 8x+18=2x+42 | | 3(x+4)=6(X-8)+12 | | 9x+8=4x+38-5 | | 35=b+30 | | 6c=42 | | 1440*5=x | | (7+6)+4=n+(6+4) | | -7-3x=8x+15 | | A=21z-2lh+2wh | | 6n+9=25 | | -9+5(9x+4)=-12 | | (9)10+4= | | 35h-2h^2=0 | | 910+4= | | (5x^2+5x-4)+(4x^2+7x+10)-(9x^2-19)= | | 2h*h=0 | | -(m+6n-12)= | | -(m+6n-12)= | | (2x-6)(3x+3)= | | 16x-3=x+27 | | -4x-10=-12 | | 5(t+1)=20 | | .3x-3x+.8=.6 | | 5t+1=20 | | 3x+2(4x-3)=3(2x-3) | | 3y+9=3(5y-1) |